Insecticide resistance dynamics in Aedes mosquitoes in Ghana - Sraku, Isaac Kwame; Owusu-Asenso, Christopher Mfum; Anisa Abdulai; Akuamoah-Boateng, Yaw; Akuamoah-Boateng, Yaw; Owusu, Faustina Adobea; Sabtiu, Abdul Rahim Mohammed; Sabtiu, Abdul Rahim Mohammed; Appiah-Kwarteng, Cornelia; Arhin, Grace Danquah; Forson, Akua Obeng; Afrane, Yaw; et al. (Gigabyte, 2025)
Arboviral diseases such as dengue, chikungunya, Zika, and yellow fever are of increasing endemicity and public health concern in Africa, with dengue representing a rapidly growing threat. Understanding the spatial distribution and insecticide resistance dynamics of Aedes vectors is critical for guiding effective control interventions. We conducted larval surveys and WHO adult susceptibility bioassays on emerged adults from January 2019 to December 2023 across ecological zones in Ghana. Bioassays revealed widespread resistance in Ae. aegypti to pyrethroids, with mortality ranging from 33.8% to 88.8% for deltamethrin and 65% to 89% for permethrin. Mortality in the 90–97% range, suggesting possible resistance, was observed in some sites, whereas Ae. aegypti from Paga, Takoradi, and Accra were susceptible to pirimiphos-methyl. Ae. vittatus populations exhibited confirmed or possible resistance to pyrethroids, while Ae. albopictus remained susceptible to all insecticides tested. Genotyping of mosquitoes (n = 887) identified high allelic frequencies of the F1534C kdr mutation in pyrethroid-resistant Ae. aegypti populations, particularly in Konongo, Navrongo, Ada, Tema, and Accra (F = 0.72–0.97). Lower frequencies were detected in Ae. albopictus (F = 0.35) and Ae. vittatus (F = 0.05–0.32). The V1016I mutation occurred in all species at variable frequencies (F = 0.02–0.80), while the V410L mutation was detected in Ae. aegypti (F = 0.30) and Ae. albopictus (F = 0.27) from Takoradi. These findings highlight widespread pyrethroid resistance in Ghanaian Aedes populations, driven primarily by target-site insensitivity, and underscore the urgent need for evidence-based integrated vector management strategies.